Manual and Automated Comparatıve Analysıs in Retıculocyte Countıng Method - Ashim Manta; Nitumani Khaklari; Gayatri Gogoi; Ricko Dharmadi Utama; Ahmad Muhlisin (Medical Laboratory Technology Journal, 2020)
The traditional method of reticulocyte count is based on microscopic evaluation of peripheral blood films. Automated processes have replaced the manual method of reticulocyte counts in most laboratories. They are readily available and give more precise results. The present study was conducted to compare the manual and automated methods of reticulocyte estimation. The study was conducted for six months, from January to June 2019, at a tertiary care center in Dibrugarh, Assam. One hundred twenty-six venous blood samples of patients were analyzed, of whom 27 were males and 99 females. Student t-test between the two methods showed a p-value of 0.41. Pearson's coefficient between the two methods showed r value =0.992. Scatter plot and Passing &Bablock regression analysis showed a positive correlation between the two methods. The present study showed a good correlation between manual and automated methods. The manual method can use the manual method of counting reticulocytes in situations of limited cost. In contrast, the automatic method can be an option when fast results and large sample sizes are required.